A Comparative Synthetic Strategy Perspective on α‐Amino Acid‐ and Non‐Amino Acid‐Derived Synthons towards Total Syntheses of Selected Natural Macrolides. Issue 23 (18th February 2020) - Kumar Manda, Srinivas Lavanya; Tripathi, Shashank; Ghoshal, Anirban; Ambule, Mayur D.; Srivastava, Ajay Kumar; Panda, Gautam
Abstract: Macrocyclic alkaloids (macrolides) and cyclopeptides have an immense range of applications in drug discovery research because of their natural abundance and potential biological and physicochemical properties. Presently, more than 100 approved drugs or clinical drug candidates contain macrocyclic scaffolds as the biologically active component. This review provides an interesting perspective about the use of amino acid‐derived chiral pools versus other methods derived from miscellaneous synthons towards the total synthesis of non‐peptidic macrolides. The synthetic routes and the key strategies involved in the total syntheses of ten natural macrolides have been discussed. Both the amino acid‐derived and non‐amino acid‐derived synthetic routes have been illustrated to present a comparative study between the two approaches. Abstract : Amino versus non‐amino acids : Synthesis of macrolides has always been challenging owing to their structural complexity. This Review provides a perspective on the use of amino acid‐derived and non‐amino acid‐derived synthons towards the synthesis of selected natural macrolides. Synthetic strategies have been assessed on the basis of overall chemical yield, reaction efficiency, and challenging stereochemical transformations.